DEVELOPING STUDENTS SPEAKING SKILL THROUGH SHORT EXPRESSION - Desi Masitoh (Department of English Education, Universitas Panca Sakti Bekasi, 2022)
This research was classroom action research (CAR) design that through short expressions to develop speaking skill of Seventh grade of SMPIT AL HIKMAH Jakarta, which amount of 20 students. It focused on developing the real condition of English teaching and learning. To recognize the scholars’ development fulfillment, the researcher used oral test in cycle I, and cycle II. Earlier than implementing exam cycle I and cycle II, the researcher carried out movement to the students through cycles. The result of cycle I had confirmed the development of students speaking ability, but that development did not complete the standard score which is 7, because of that the researcher persevered to use cycle II. And in the test cycle II finally the scholars showed the development drastically. The result the students speaking score at pre-cycle to cycle II are increasing. In cycle I by 62% and improved in cycle II to 85%. The results indicate there is a development in students speaking ability through short expression. It could be concluded that developing speaking ability through short expression are powerful and successful.